Longitudinal study of dental caries in Brazilian children aged from 12 to 30 months - ANA ISABEL FONSECA SCAVUZZI, ARNALDO DE FRANÃƒÆ’Ã¢â‚¬Â¡A CALDAS JUNIOR, GERALDO, MÃƒÆ’Ã‚ÂRCIA MARIA (IAPD and Blackwell, 2007)
The purpose of the present study was to investigate caries in a sample of young children in Brazil.